Correction: Phosphorylation of bio-based compounds: the state of the art. Issue 7 (28th January 2016) - Illy, Nicolas; Fache, Maxence; Ménard, Raphaël; Negrell, Claire; Caillol, Sylvain; David, Ghislain
Abstract : Correction for 'Phosphorylation of bio-based compounds: the state of the art' by Nicolas Illy, et al., Polym. Chem., 2015, 6, 6257–6291.